Audit of Neonatal Outcome in Tertiary Care Hospital. - Rashid, Shaista; Iqbal , Asma; Nadeem, Shabnam (International Journal of Endorsing Health Science Research, 2021)
Background: Every year, 2.7 million stillbirths occur worldwide, mostly in developing countries. The United Nations Sustainable Development Goals (SDGs) include reducing childhood mortality under five years of age. Perinatal death audit is an intervention to reduce preventable neonatal mortality. The aim of this study was to determine the Perinatal Mortality Rate (PMR) and the factors responsible for perinatal deaths at a Tertiary Care Hospital in Karachi-Pakistan. Methodology: This was a prospective study of all the stillbirths and early neonatal deaths in Abbasi Shaheed Hospital Karachi, Gynecology Unit I. Details of each perinatal death were filled in the standard form. We used Aberdeen Obstetric classification to classify causes of perinatal deaths. Results: There were 1627 deliveries and 43 perinatal deaths during the study period. Our study's perinatal mortality rate was 27.14/1000 births, and the stillbirth rate was 13.25/1000 births. Antepartum hemorrhage (APH), pregnancy-induced hypertension (PIH) and anemia were the common causes of perinatal deaths. Conclusion: Antepartum hemorrhage, pregnancy-induced hypertension and anemia are the leading causes of perinatal deaths. Most of these complications can be reduced by educating women and providing effective antenatal care.